Unveiling the Hyper-Rayleigh Regime of the Fluctuating Two-Ray Fading Model - Celia Garcia-Corrales; Unai Fernandez-Plazaola; Francisco J. Canete; Jose F. Paris; F. Javier Lopez-Martinez (IEEE Access, 2019)
The recently proposed fluctuating two-ray (FTR) model is gaining momentum as a reference fading model in scenarios where two dominant specular waves are present. Despite the numerous research works devoted to the performance analysis under FTR fading, little attention has been paid to effectively understanding the interplay between the fading model parameters and the fading severity. According to a new scale defined in this work, which measures the hyper-Rayleigh character of a fading channel in terms of the amount of fading, the outage probability and the average capacity, we see that the FTR fading model exhibits a full hyper-Rayleigh behavior. However, the two-wave with diffuse power fading model from which the former is derived has only strong hyper-Rayleigh behavior, which constitutes an interesting new insight. We also identify that the random fluctuations in the dominant specular waves are ultimately responsible for the full hyper-Rayleigh behavior of this class of fading channels.